Changes in health-related lifestyles and food insecurity and its association with quality of life during the COVID-19 lockdown in Malaysia - Aryati Ahmad; Mohd Razif Shahril; Nadiah Wan-Arfah; Wan Azdie Mohd Abu Bakar; Abu Bakar; Carmen Piernas; Pei Lin Lua (BMC, 2022)
Abstract Background The pandemic of SARS CoV2 virus has severely impacted the entire world population. The lockdown imposed during the pandemic has created enormous challenges particularly on the health, economic and social life of most individuals. This study aimed to investigate the changes in health-related lifestyle and food security during the lockdown and how they influenced the quality of life (QoL) of Malaysian adults. Methods An online survey using a structured questionnaire consisting of sociodemographic, body weight, diet quality, physical activity, sleep quality, food insecurity, and QoL was conducted among adult respondents across Malaysia. Multivariate linear regression analyses were conducted to assess the associations between the changes in each component and QoL based on the total score before and during the lockdown. Results A total of 759 valid responses were included in the final analysis (75% female and 24.5% male). There was a significant improvement in diet quality during the lockdown while sleep quality and food insecurity worsened significantly. As for physical activity, metabolic equivalents (METs) in moderate activity increased significantly, whilst there was a significant decrease in the METs in walking and total minutes spent on physical activity during the lockdown. Overall, independent of age, gender, ethnicity, and religion, there were significant associations between QoL during lockdown and changes in BMI, METs of moderate activity, sleep quality, and food insecurity. Conclusions The unprecedented COVID-19 outbreak and the lockdown measure during the pandemic have caused significant negative changes in health-related lifestyles and affected the QoL of Malaysian adults. Despite the new norms and rules to prevent disease transmission, efforts to maintain a healthy lifestyle and food security among the population must be rolled out to improve the QoL and prevent further adverse mental and physical health outcomes.